MULTIGROUP ANALYSIS IN SUPPLY CHAIN PERFORMANCE - Erna Mulyati (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2020)
This study aims to examine differences in private and government third-party logistics companies in Indonesia in terms of improving supply chain performance. In this research, supply chain performance testing is influenced by collaboration, radical innovation, and incremental innovation. The sample used is the third-party logistics industry in West Java and DKI Jakarta, totaling 100, which is divided into private third-party logistic companies and government-owned third-party logistics companies. The results showed that there are differences in the effects of collaboration. There is supply chain performance where there are differences in the influence of collaboration and radical innovation on supply chain performance between private companies and government. There is no difference in the influence of collaboration and incremental innovation on supply chain performance between private companies and the government. The findings of this study indicate that radical and incremental innovation acts as a partial mediation on the effect of collaboration on supply chain performance in private and government companies.